Global susceptibility and response to noncommunicable diseases - Allen, L; Hatefi, A; Nugent, R; Bollyky, T (World Health Organisation, 2018)
Globalization and human interdependence have created immeasurable value for humanity. These forces, however, also provide channels for health risks to spread throughout the world. Global functions for health, such as international partnerships or research and development, are a rational response to global health risks like pandemics or globalized supply chains. Self-interest compels governments – or donors – to provide global functions even though their benefits are widely shared the world over.